2016
DOI: 10.1007/s12035-016-9764-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Significance of Circulating microRNAs in Cerebrospinal Fluid of Acute Encephalitis Patients Infected with Japanese Encephalitis Virus

Abstract: Changes in circulating microRNAs (miRNAs) in the cerebrospinal fluid (CSF) have been associated with different neurological diseases. Here, we presented results of a pilot study aimed at determining the feasibility of detecting miRNAs in the CSF of Japanese Encephalitis virus (JEV) infected individuals with acute encephalitis syndrome (AES). We demonstrated the circulating miRNA profile in CSF of acute encephalitis patients infected with JEV. Using a quantitative real-time PCR-based miRNA array, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…In a study investigating brain glioblastoma, miR-21-5p has been highly expressed 19. Moreover, a high expression in CSF in patients infected with Japanese encephalitis virus was detected 12. Similarly, in our study, we found that the expression of miR-21-5p was upregulated in the CSF of patients with neurosyphilis, which confirms that miR-21-5p is an miRNA closely related to CNS tumours and inflammation.…”
Section: Discussionsupporting
confidence: 86%
“…In a study investigating brain glioblastoma, miR-21-5p has been highly expressed 19. Moreover, a high expression in CSF in patients infected with Japanese encephalitis virus was detected 12. Similarly, in our study, we found that the expression of miR-21-5p was upregulated in the CSF of patients with neurosyphilis, which confirms that miR-21-5p is an miRNA closely related to CNS tumours and inflammation.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, the previous and current study indicates that these microRNAs might be relevant to JEV infection in human microglial cells. [36][37][38] Moreover, there are two pairs of microRNA and gene targets, which were consistent with the previous report. 13,39 Nevertheless, there are several other differentially expressed microRNAs, which have not been reported earlier in case of JEV infection in microglia, and might be novel to JEV infection.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, several of the differentially expressed microRNAs were found common to the previous published reports for example, miR‐21, miR‐101‐3p, miR‐32‐5p, miR‐4695‐3p, miR‐432‐5p, miR‐205, miR‐450b‐3p, miR‐3613‐5p, miR‐190a, miR‐299‐5p, miR‐4286,miR‐1264, miR‐193a‐3p, miR‐138, miR‐3182, miR‐19a, miR‐1260b, miR‐3074, miR‐374b, miR‐588, miR‐597, miR‐487b, miR‐676, miR‐196a, miR‐539‐3p, miR‐802, miR‐629‐3p,miR‐301a‐3p, miR‐3156, miR‐222‐5p, and miR‐29b‐3p. Consequently, the previous and current study indicates that these microRNAs might be relevant to JEV infection in human microglial cells . Moreover, there are two pairs of microRNA and gene targets, which were consistent with the previous report .…”
Section: Discussionsupporting
confidence: 92%
“…The genes or pathways affected by these are being worked out; some of them are pathways in cancer, the neurotrophin signaling pathway, the Toll-like receptor signaling pathway, the Notch signaling pathways, and the JAK-STAT signaling pathway. In exosomes isolated from cerebrospinal fluid of JEV-infected human subjects, miR-21-5p, miR-150-5p, and miR-342-3p levels were found to be elevated, a trend that is also observed in infected mice brain 31 . Bioinformatic analysis for putative target genes of these three miRNAs indicated the involvement of transforming growth factor-beta (TGF-β), nerve growth factor (NGF), axon guidance, and mitogen-activated protein kinase (MAPK) signaling pathways 31 .…”
Section: Micrornas: the New Players In The Fieldmentioning
confidence: 60%
“…In exosomes isolated from cerebrospinal fluid of JEV-infected human subjects, miR-21-5p, miR-150-5p, and miR-342-3p levels were found to be elevated, a trend that is also observed in infected mice brain 31 . Bioinformatic analysis for putative target genes of these three miRNAs indicated the involvement of transforming growth factor-beta (TGF-β), nerve growth factor (NGF), axon guidance, and mitogen-activated protein kinase (MAPK) signaling pathways 31 . Thus, a vista of novel information has begun to be available that would help in better understanding the molecular pathology of JE and hopefully also in developing newer therapeutic interventions.…”
Section: Micrornas: the New Players In The Fieldmentioning
confidence: 60%